Power Management of Autonomous Microgrids with Distributed Generations and Energy Storage Systems - Hosseinimehr, Tahoura (Curtin University, 2017)
This thesis is mainly focused on the development of reliable power management strategics for islanded IVIGs. The main objectives of the proposed strategics are to provide accurate active and reactive power sharing, maintain system power balance, coordinate energy storage systems with distributed energy resources, enhance lifetime of the batteries by controlling their state of charge, and efficiently employ renewable energy sources such as photovoltaic (PV) systems in the lVIG, etc.